New and non-indigenous species of Bryozoa from Iberian waters - Reverter-Gil, Oscar; Souto, Javier (European Journal of Taxonomy, 2023)
Iberian material originally identified as Hincksina flustroides is revised and five different species are now identified: the Atlantic species Hincksina flustroides is present to the NW of the Iberian Peninsula, whilst the Mediterranean species Hincksina synchysia is here reported for the first time in Iberian waters. Two new species of Hincksina are described, one from the Strait of Gibraltar area, and another from the Alboran Sea, whereas another colony from this area actually corresponds to Hincksina longispinosa. A new description of Electra angulata is given, based on the original and other historical material, as well as on newly collected colonies. The taxonomic position of the species in the genus Arbopercula is discussed, and the diagnosis of the genus itself is amended. Finally, a new species of Caberea is described from deep waters off the north Iberian coast.